Country of Football : Politics, Popular Culture, and the Beautiful Game in Brazil. - Fontes, Paulo (Hurst, 2014)
Brazil has done much to shape football/soccer, but how has soccer shaped Brazil? Despite the political and social importance of the beautiful game to the country, the subject has hitherto received little attention. This book presents groundbreaking work by historians and researchers from Brazil, the United States, Britain and France, who examine the political significance, in the broadest sense, of the sport in which Brazil has long been a world leader. The authors consider questions such as the relationship between soccer, the workplace and working class culture; the formation of Brazilian na.